1999
DOI: 10.1093/genetics/152.4.1407
|View full text |Cite
|
Sign up to set email alerts
|

UV Stimulation of Chromosomal Marker Exchange in Sulfolobus acidocaldarius: Implications for DNA Repair, Conjugation and Homologous Recombination at Extremely High Temperatures

Abstract: The hyperthermophilic archaeon Sulfolobus acidocaldarius exchanges and recombines chromosomal markers by a conjugational mechanism, and the overall yield of recombinants is greatly increased by previous exposure to UV light. This stimulation was studied in an effort to clarify its mechanism and that of marker exchange itself. A variety of experiments failed to identify a significant effect of UV irradiation on the frequency of cell pairing, indicating that subsequent steps are primarily affected, i.e., transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In both cases, other possible explanations, such as transduction by virus particles, cross-feeding, and genetic complementation by way of diploid heterozygous cell formation, were ruled out and in both cases cell-cell contact, including actual cell aggregation, was visible. Shortly after these observations it was noted that exposure to UV radiation greatly increases DNA exchange (117,155).…”
Section: Molecular Mechanisms Of Genetic Exchange In Archaea Natural ...mentioning
confidence: 99%
“…In both cases, other possible explanations, such as transduction by virus particles, cross-feeding, and genetic complementation by way of diploid heterozygous cell formation, were ruled out and in both cases cell-cell contact, including actual cell aggregation, was visible. Shortly after these observations it was noted that exposure to UV radiation greatly increases DNA exchange (117,155).…”
Section: Molecular Mechanisms Of Genetic Exchange In Archaea Natural ...mentioning
confidence: 99%
“…Further work showed that selected marker transfer occurs in small discontinuous patches that are dependent on minimal homology ( Hansen et al, 2005 ). In most studies, ME is up-regulated with DNA damaging agent exposure leading to the current hypothesis that ME is a mechanism for DNA repair ( Schmidt et al, 1999 ; Ajon et al, 2011 ; van Wolferen et al, 2015 , 2016 , 2020 ; Feng et al, 2018 ; Schult et al, 2018 ; Sun et al, 2018 ). It has been experimentally shown that in Sulfolobus acidocaldarius , exposure to DNA damaging agents results in induced type IV pilin-mediated cell aggregation ( van Wolferen et al, 2016 ; Sun et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%